A virtual logistics network and an e-hub as a competitive approach for small to medium size companies - Chang, Elizabeth; Dillon, Tharam S.; Gardner, W.; Talevski, A.; Rajugan, R.; Kapnoullas, T. (Springer-Verlag, 2003)
As small to medium sized logistics companies strive to be more competitive with the larger ones, computer processes will progressively be carried out differently than in the traditional manner. Progressively more and more computation will occur on the Internet rather than just make use of it as a gateway. Programs will be distributed throughout a network and the World Wide Web and work together in a highly developed manner. A virtual logistics network provides an organisational framework for collaboration in this manner is proposed. In this paper we propose a virtual logistics network that provides an organizational framework for collaboration between small to middle sized companies. This employs an e-hub structure utilizing XML based mobile agents to provide seamless integration between isolated information systems for small to medium sized logistic providers.